Effect of involving certified healthcare assistants in primary care in Germany: a cross-sectional study - Senft, Jonas; Wensing, Michel; Poß-Doering, Regina; Szecsenyi, Joachim; Laux, Gunter (BMJ open, 2019)
Objectives Growing prevalence of chronic diseases and limited resources are the key challenges for future healthcare. As a promising approach to maintain high-quality primary care, non-physician healthcare professionals have been trained to broaden qualifications and responsibilities. This study aimed to assess the influence of involving certified healthcare assistants (HCAs, German: Versorgungsassistent/in in der Hausarztpraxis) on quality and efficacy of primary care in Germany. - Design Cross-sectional study. - Setting Primary care. - Participants Patients insured by the Allgemeine Ortskrankenkasse (AOK) statutory health insurer (AOK, Baden-Wuerttemberg, Germany). - Interventions Since 2008 practice assistants in Germany can enhance their professional education to become certified HCAs. - Primary and secondary outcome measures Claims data related to patients treated in practices employing at least one HCA were compared with data from practices not employing HCAs to determine frequency of consultations, hospital admissions and readmissions. Economic analysis comprised hospitalisation costs, prescriptions of follow-on drugs and outpatient medication costs. - Results A total of 397 493 patients were treated in HCA practices, 463 730 patients attended to non-HCA practices. Patients in HCA practices had an 8.2% lower rate of specialist consultations (p<0.0001), a 4.0% lower rate of hospitalisations (p<0.0001), a 3.5% lower rate of readmissions (p=0.0463), a 14.2% lower rate of follow-on drug prescriptions (p<0.0001) and 4.7% lower costs of total medication (p<0.0001). No difference was found regarding the consultation rate of general practitioners and hospital costs. - Conclusions For the first time, this high-volume claims data analysis showed that involving HCAs in primary care in Germany is associated with a reduction in hospital admissions, specialist consultations and medication costs. Consequently, broadening qualifications may be a successful strategy not only to share physicians’ work load but to improve quality and efficacy in primary care to meet future challenges. Future studies may explore specific tasks to be shared with non-physician workforces and standardisation of the professional role.
Gesehen am 14.04.2020